The Effects of Intervention on Muslims Adolescents: Research Findings and Future Directions - Janon, Nazariah Shar'ie (IIUM Press, 2021)
This chapter aims to demonstrate the role of intervention on resilience. A total of 31 adolescents from Gombak, Selangor had participated in an experimental study that participants had divided into two groups (n=16 experimental group and n=15 in the control group). Those in the experimental group were exposed to the intervention programme whereas those in the control group were not. Results indicated that there are no significant effect of the intervention on the adolescents' resilience after the programme. Although the score of resilience in the post-assessment increased but the differences before and after the programme is not significant. Thus, this may be subject to other variables that may include personal disposition traits, attitude, learning and the soul of the Muslim adolescents. The chapter futher discuss the needs of intervention program for building resilience in Muslim adolescents.